Investigation of the microbial community in the Odisha hot spring cluster based on the cultivation independent approach - Singh, Archana (Genom Data, 2016)
Deulajhari hot spring is located in the Angul district of Odisha. The significance of this hot spring is the presence of the hot spring cluster adjacent to the cold spring which attracts the attention of microbiologists to understand the role of physio-chemical factors of these springs on bacterial community structure. Next-generation sequencing technology helps us to depict the pioneering microflora of any ecological niche based on metagenomic approach. Our study represents the first Illumina based metagenomic study of Deulajhari hot spring DH1, and DH2 of the cluster with temperature 65 °C to 55 °C respectively establishing a difference of 10 °C. Comprehensive study of microbiota of these two hot springs was done using the metagenomic sequencing of 16S rRNA of V3‐V4 region extracting metagenomic DNA from the two hot spring sediments. Sequencing community DNA reported about 28 phyla in spring DH1 of which the majority were Chloroflexi (22.98%), Proteobacteria (15.51%), Acidobacteria (14.51%), Chlorobi (9.52%), Nitrospirae (8.54%), and Armatimonadetes (7.07%), at the existing physiochemical conditions like; temperature 65 °C, pH 8.06, electro conductivity 0.020 dSm(− 1), and total organic carbon (TOC) 3.76%. About 40 phyla were detected in cluster DH2 at the existing physiochemical parameters like temperature 55 °C, pH 8.10, electro conductivity 0.019 dSm(− 1), and total organic carbon (TOC) 0.58% predominated with Chloroflexi (41.98%), Proteobacteria (10.74%), Nitrospirae (10.01%), Chlorobi (8.73%), Acidobacteria (6.73%) and Planctomycetes (3.73%). Approximately 68 class, 107 order, 171 genus and 184 species were reported in cluster DH1 but 102 class, 180 order, 375 genus and 411 species in cluster DH2. The comparative metagenomics study of the Deulajhari hot spring clusters DH1, and DH2 depicts the differential profile of the microbiota. Metagenome sequences of these two hot spring clusters are deposited to the SRA database and are available in NCBI with accession no. SRX1459734 for DH1 and SRX1459735 for DH2.